Efficient Frontier Analysis of Islamic and Conventional Bank Stock Portfolios: Evidence from Four IDX-Listed Issuers Using the Markowitz Model - Dede Irman; Alim Jaizul Wahid (Research Collaboration Community (RCC), 2026)
This study investigates and compares the portfolio performance of Islamic and conventional bank stocks listed on the Indonesia Stock Exchange (IDX) using the Markowitz Mean-Variance optimization model. Four issuers were selected: PT Bank Rakyat Indonesia Tbk (BBRI), PT Bank Mandiri Tbk (BMRI), PT Bank Rakyat Indonesia Syariah Tbk (BRIS), and PT Bank Pembangunan Daerah Banten Tbk (BPAA), representing two conventional and two Islamic banking stocks respectively. Daily closing price data spanning from January 2021 to December 2023 (756 trading days) were employed to compute expected returns, variance, covariance, and correlation coefficients. Two optimal portfolios were constructed for each category: the Minimum-Variance Portfolio (MVP) and the Maximum-Sharpe Portfolio (MSP). Performance evaluation was carried out through multiple metrics including the Sharpe Ratio, Treynor Ratio, Jensen's Alpha, and Sortino Ratio. Results indicate that Islamic bank portfolios consistently outperform conventional bank portfolios on a risk-adjusted basis. The Maximum-Sharpe Islamic portfolio achieved a Sharpe Ratio of 1.765 compared to 1.342 for its conventional counterpart. These findings suggest that Islamic banking stocks, with their inherently lower leverage and prohibition on speculative instruments, exhibit more favourable risk-return characteristics, providing actionable insights for investors seeking Shariah-compliant investment alternatives.